Microwave circulator design - Linkhart, Douglas K. (Artech House microwave library., 2014)
"Circulator design has advanced significantly since the first edition of this book was published 25 years ago. The objective of this second edition is to present theory, information, and design procedures that will enable microwave engineers and technicians to design and build circulators successfully. This resource contains a discussion of the various units used in the circulator design computations, as well as covers the theory of operation. This book presents numerous applications, giving microwave engineers new ideas about how to solve problems using circulators. Design examples are provided, which demonstrate how to apply the information to real-world design tasks."--